A fuzzy approach to service quality diagnosis. Issue 1 (2nd February 2015) - Saeida Ardakani, Saeid; Nejatian, Majid; Farhangnejad, Mohammad Ali; Nejati, Mehran
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to identify service quality dimensions that could enhance the level of services provided by a variety of carriers and rank them, accordingly. Design/methodology/approach – This research aims to identify service quality dimensions that could enhance the level of services provided by a variety of carriers and rank them, accordingly. Findings – The results show that "safety, " "timeliness, " and "variety and type of airplane" are the most important service quality criteria from the passengers' viewpoint. It also indicates that the most and least important dimensions of service quality are "tangibles" and "responsiveness, " respectively. The results ranked the airlines from one to three as Emirates Airline, Mahan Air, and Iran Air. Originality/value – Most of the service quality criteria are descriptive and are stated using lingual expressions (cardinal or ordinal scales). Therefore, evaluation of perceptions and expectations of customers regarding service quality using non-fuzzy methods ignores the ambiguity involved in individual judgments.